2009
DOI: 10.1007/s00249-009-0558-2
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of actin filament turnover for fitting FRAP data

Abstract: A novel mathematical model of the actin dynamics in living cells under steady-state conditions has been developed for fluorescence recovery after photobleaching (FRAP) experiments. As opposed to other FRAP fitting models, which use the average lifetime of actins in filaments and the actin turnover rate as fitting parameters, our model operates with unbiased actin association/dissociation rate constants and accounts for the filament length. The mathematical formalism is based on a system of stochastic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, using this method to compare two curves does not directly lead to a p -value but the significance is estimated by other means. More elaborate means of analysis are also found where fitting is performed to a stochastic model of actin treadmilling (Halavatyi et al, 2010). These models work well in in silico simulations but fitting measured data to six different parameters without fixed values is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, using this method to compare two curves does not directly lead to a p -value but the significance is estimated by other means. More elaborate means of analysis are also found where fitting is performed to a stochastic model of actin treadmilling (Halavatyi et al, 2010). These models work well in in silico simulations but fitting measured data to six different parameters without fixed values is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…This recovery can occur through the diffusion of monomeric EGFP-Actin or through nucleation of EGFP-Actin at the junctions. As diffusive recovery occurs within 50 ms (Fritzsche et al, 2013), we assumed that monomeric EGFP-Actin distribution was homogeneous (Halavatyi et al, 2010) and that the recovery of the mobile EGFP-Actin fraction was a result of F-actin polymerization. Thus, our FRAP study revealed a mobile pool of dynamic F-actin with high turnover at EC junctions.…”
Section: Formin Activity Maintains a Pool Of Dynamic F-actin At Endotmentioning
confidence: 99%
“…For example, one method tailored specifically to actin called sequential fluorescence decay after photoactivation (sFDAP) uses sequential photoactivation in a single region of the cell in order to obtain information about the local G-actin concentration and how it changes with respect to extracellular stimuli (Higashida et al, 2013; Kiuchi et al, 2011). However, one problem with deriving accurate information from photoactivation or photobleaching experiments is that the analysis often fails to account for all of the complex real-world details of an experiment (Carrero et al, 2003; Halavatyi et al, 2010; Sprague et al, 2004; Tardy et al, 1995). These include, but are not limited to: non-isotropic diffusion due to specific cell morphology, a substantial loss of information due to the delay between photoactivation and imaging recording, and the fact that photoactivation is non-instantaneous.…”
Section: Introductionmentioning
confidence: 99%